Varied hypoxia adaptation patterns of embryonic brain at different development stages between Tibetan and Dwarf laying chickens - Qiguo Tang; Runjie Yu; Yubei Wang; Fuyin Xie; Hao Zhang; Changxin Wu; Meiying Fang (BMC Genomics, 2023)
Abstract Background Tibetan chickens (Gallus gallus; TBCs), an indigenous breed distributed in the Qinghai-Tibet Plateau, are well adapted to the hypoxic environment. Currently, the molecular genetic basis of hypoxia adaptation in TBCs remains unclear. This study investigated hypoxia adaptation patterns of embryonic brain at different development stages by integrating analysis of the transcriptome with our previously published metabolome data in TBCs and Dwarf Laying Chickens (DLCs), a lowland chicken breed. Results During hypoxia, the results revealed that 1334, 578, and 417 differentially expressed genes (DEGs) (|log2 fold change|>1, p-value < 0.05) on days 8, 12, and 18 of development, respectively between TBCs and DLCs. Gene Ontology (GO) and pathway analyses revealed that DEGs are mainly related to metabolic pathways, vessel development, and immune response under hypoxia. This is consistent with our metabolome data that TBCs have higher energy metabolism than DLCs during hypoxia. Some vital DEGs between TBCs and DLCs, such as EPAS1, VEGFD, FBP1, FBLN5, LDHA, and IL-6 which are involved in the HIF pathway and hypoxia regulation. Conclusion These results suggest varied adaptation patterns between TBCs and DLCs under hypoxia. Our study provides a basis for uncovering the molecular regulation mechanism of hypoxia adaptation in TBCs and a potential application of hypoxia adaptation research for other animals living on the Qinghai-Tibet Plateau, and may even contribute to the study of brain diseases caused by hypoxia.